THE IMPACT OF US MONETARY POLICY AND STOCK MARKETS TOWARD INDONESIA STOCK MARKETS - Abduh, Muhamad (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2011)
The aim of this paper is to examine the interdependence revulsion of Indonesia Stock Markets (JCI) with the changes in US Monetary policy and Stock Markets (DJCI). The methodology used in this study is time series econometric techniques i.e. the unit root test, cointegration test, Granger’s causality and Vector Error Correction Model (VECM). The result reveals a short-term and long-term dynamic relationship between the US stock markets and the Indonesia one. A 1 percent increase in US stock markets contributes to Indonesia stock markets by 0.4 percent over the next 10 months. One of the policy implications is that the authority of Indonesia stock markets should strengthen and improve their regulations so that the susceptible of the stock markets can be minimized.